2015
DOI: 10.1038/cdd.2014.214
|View full text |Cite
|
Sign up to set email alerts
|

p73 is required for endothelial cell differentiation, migration and the formation of vascular networks regulating VEGF and TGFβ signaling

Abstract: Vasculogenesis, the establishment of the vascular plexus and angiogenesis, branching of new vessels from the preexisting vasculature, involves coordinated endothelial differentiation, proliferation and migration. Disturbances in these coordinated processes may accompany diseases such as cancer. We hypothesized that the p53 family member p73, which regulates cell differentiation in several contexts, may be important in vascular development. We demonstrate that p73 deficiency perturbed vascular development in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 63 publications
7
62
0
6
Order By: Relevance
“…Consistently, a third group reported that constitutive p73 deficiency (both TAp73 and DNp73) impairs vascular development in mouse retina. In particular, DNp73 [the predominantly expressed isoform in endothelial cells (EC)], but not TAp73 (poorly expressed), promotes in vitro EC tube formation and migration as well as in vivo vascularization of tumor xenografts [31]. Overall, independent groups have consistently reported opposite roles for TAp73 and DNp73, respectively, in repressing and promoting angiogenesis.…”
Section: Reviewmentioning
confidence: 98%
“…Consistently, a third group reported that constitutive p73 deficiency (both TAp73 and DNp73) impairs vascular development in mouse retina. In particular, DNp73 [the predominantly expressed isoform in endothelial cells (EC)], but not TAp73 (poorly expressed), promotes in vitro EC tube formation and migration as well as in vivo vascularization of tumor xenografts [31]. Overall, independent groups have consistently reported opposite roles for TAp73 and DNp73, respectively, in repressing and promoting angiogenesis.…”
Section: Reviewmentioning
confidence: 98%
“…p53, TAp73 and TAp63 have been described to counteract HIF-1 activity affecting its stability though direct or indirect mechanisms Amelio and Melino, 2012;Fernandez-Alonso et al, 2015;Montagner et al, 2012;Ravi et al, 2000). These signalling generate oxygen-independent regulation of HIF-1 that impact on the tumorigenic potential of cancer cells, affecting angiogenesis, metabolism and metastasis .…”
Section: Oxygen Tension Hypoxia Inducible Factors and Ageing Relatedmentioning
confidence: 99%
“…Moreover, expression of p73 was increased with higher degrees of tumour malignancy, supporting the theory that excessive levels contribute to tumour progression, similar to our previous observations 42. An earlier study using a melanoma cell line reported that overexpression of p73 enhances tumour progression due to its pro-angiogenic capacity via regulation of pro-angiogenic factors, such as transforming growth factor-β and vascular endothelial growth factors 62. Sablina et al observed that increased p73 transcriptional activity is accompanied by human lung carcinoma cell migration 63.…”
Section: Discussionmentioning
confidence: 99%